Per una teoria kantiana della traduzione - D’Agostino, Pierluigi (Con-Textos Kantianos. International Journal of Philosophy, 2023)
It is almost universally accepted that Kant had a theory of language, or that Kant’s theory of experience and knowledge can lay the foundation for reconstructing a Kantian theory of language. Most debatable is whether Kant had something to say on the philosophical problem of translation. In this paper I argue that Kant’s philosophical theory allows dealing with the problem of translation, though recognising it presupposes that we realise Kant could not be content with a short argument for translatability (the argument that the human beings share a universal structure of thought, which is reliably mirrored in language; therefore natural languages are, in principle, symmetrically translatable). Rather, a Kantian theory of translation must take into account the very complex nature of common-sense, and what is grounded on it, i.e., intersubjective communicability and culture.